Witness preparation in the ICC: an opportunity for principled pragmatism - Jackson, John D.; Brunger, Yassin M. (Oxford University Press, 2015)
In January 2013, Trial Chamber V of the International Criminal Court (ICC) in the cases of William Ruto and Joshua Sang and of Francis Muthaura and Uhuru Kenyatta, collectively known as the ‘Kenya decisions’, made a marked departure from the firm prohibition on ‘witness proofing’ established by the ICC's Pre-Trial and Trial Chamber I in the Lubanga decisions. This reversal illustrates the polarization of an issue that has caused considerable controversy in the international legal community and demonstrates the challenges faced by the Court in navigating such a controversy. While the practice may be viewed as a fault line between two different procedural cultures, forever destined to be subject to debate, this article explores an alternative view, examining the reasons for this turnaround and proposing an approach based on ‘principled pragmatism’. In doing so, it considers whether witness preparation is coming to be regarded as a necessary part of ICC practice.